DEVELOPMENT OF A PROJECT-BASED LEARNING MODULE FOR STYLE AND LOOK IN FASHION VOCATIONAL HIGH SCHOOL - Yosi Rizal (Home Economics Journal, 2026)
Basic Fashion Design is an essential competency for Fashion Vocational High School to achieve competence in fashion industry. However, this remains a significant challenge, as it requires the integration of 21st-century skills in developing relevant learning materials. This study aims to develop a Project-Based Learning module for achieving learning outcomes in drawing style and look and to enhance students’ creativity in Fashion Vocational High School. This research employed the Research and Development method using the Borg and Gall model, which consists of ten stages. Data were collected through interviews, questionnaires, and observation sheets, all of which were validated by experts with very high Aiken’s V values. The results showed that the developed Project-Based Learning module was categorized as “Very Good” based on expert, teacher, and student evaluations. The experimental class demonstrated higher improvement, with the mean score increasing from 1.974 (pre-test) to 3.09 (post-test), compared to the control class which increased from 2.017 to 2.50. The difference was statistically significant (α < 0.05), indicating that the module was effective in enhancing students’ creativity. Therefore, the Project-Based Learning module is proven to be valid and effective in stimulating students’ creativity in achieving the intended learning outcomes.